DẪN LIỆU BƯỚC ĐẦU VỀ BỘ RẾT LỚN (SCOLOPENDROMORPHA) Ở VƯỜN QUỐC GIA CÁT BÀ - Lê, Xuân Sơn; Nguyễn, Đức Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PRELIMINARY DATA ON THE LARGE CENTIPEDES (SCOLOPENDROMORPHA) OF THE CAT BA NATIONAL PARKThe work presents the preliminary data of the large centipedes in the Cat Ba National Park based on field surveys from June 2013 to June 2014. A total of 14 scolopendromorpha species belonging to 3 genera and 1 family has been recorded there. Two common species Ostotigmus spinosus and Ostotigmus sp.3 have been found in almost all habitats. Among 3 recorded genera, Otostigmus is the most diverse genus with 10 species (accounts for 71.43% of total species).The species composition in the rainy season is higher than that in the dry season. The most obvious difference can be observed in the genus Otostigmus with 10 species (rainy season) compared with 3 species (dry season). No species belong to genera Scolopendra and Ethmostigmus were found in the dry season.